IMPLEMENTATION OF INTERACTIVE MULTIMEDIA-BASED MICROLEARNING LEARNING WITH THE DISCOVERY LEARNING MODEL TO INCREASE THE CREATIVITY OF THINKING OF VOCATIONAL STUDENTS - Aulia, Tamara Qolbiyatul; Wahyudin, Wahyudin; Junaeti, Enjun (Universitas Pendidikan Indonesia, 2023)
Logic gates are one of the materials in grade 10 vocational high school. Based on observations, students are having difficulties learning logic gates. The proposed solution to this problem is implementing Interactive Multimedia-based Microlearning. Microlearning divide learning content into small and focused segments which is easier for the students. The learning model used is Discovery Learning. The method used is RD (Research and Development) and One Group Pretest–Posttest research design. The subjects in this research are students of class X RPL 2 at SMK Bina Wisata Lembang that consisted of 30 students. The results of this study proved that there is an increase in student creativity based on the pretest and posttest. The increase in students' creative thinking after using this learning media has an average gain of 0.56 which interpreted as a level of effectiveness of